The role of wall deposition and re‐entrainment in swirl spray dryers. Issue 6 (29th March 2015) - Francia, Víctor; Martín, Luis; Bayly, Andrew E.; Simmons, Mark J. H.
<x xml:space="preserve">Abstract</x> A new experimental method is outlined to study fouling in spray dryers and similar devices. In essence, it makes the deposits traceable so that one can quantify the material that comes off the walls, how long it remains there and how the deposits agglomerate with particles in the air. This paper investigates a countercurrent swirl spray dryer of detergent and provides sound evidence that fouling is a dynamic process: clusters form and break at the walls renewing an active layer of deposits. Remarkably, the wall generates >20% of the product and most of the large granules, and increases drastically the residence time of the powder. The assumptions of current numerical models are clearly invalid (i.e. particles rebound at the wall or deposit indefinitely). Several re‐entrainment mechanisms and their times scales are identified in this work, and accordingly, a new general framework to describe fouling in spray dryers is proposed. © 2015 American Institute of Chemical Engineers AIChE J, 61: 1804–1821, 2015